Anthropological Perspective on the Decision-Making Process in Environmental Protection - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2020)
The systemic perspective on environmental action adopted in the paper, allows in this thematic area, issues related to the decision-making process. Due to the current crisis affecting human-environment relationships, these issues call for special attention and specific solutions. Against this backdrop, the paper draws on selected patterns, which constitute a point of reference in the formulation of the decision-making process, namely, the Deming Cycle, and the control system worked out by Marian Mazur. Among the manifold determinants of the decision-making process, special emphasis is put on the anthropological one, with reference to the approach proposed by Michał Gierycz. In turn, the idea of oikophilia, as presented by Roger Scruton, has been used as an exemplification of the discussed issues. More specifically, an attempt has been made to determine the influence of the adopted anthropological perspective on the shape and course of the decision-making process, which is the aim of the study. The paper analyses further how a defined profile of the performer, influences the structure and course of the decision-making process in environmental protection. The conducted analyses enable the formulation of a postulate, in order that the adopted vision of the decision-maker, should be treated as a point of reference in the design and construction of a methodology for environmental protection.